Stroke in young among exposed to high altitude: prospective observational study in Eastern India - Kumar, Dheeraj; Singh, Rajendra Pal; Khan, S. Ashraf (International Journal Of Community Medicine And Public Health, 2020)
Background: High altitude deployment for longer duration is a usual event among armed forces personnel. Despite our knowledge and understanding about the risk factors and treatment, stroke still remains the second leading cause of death worldwide. Present study was carried out at a teaching hospital in India, where many soldiers from high altitude area in Eastern India were referred for super speciality care. Our objective was to study the various clinical presentations and risk factors in patients of stroke in age group 15-49 years having longer duration of stay at high altitude. Methods: Patients of stroke between ages 15-49 years, referred to a tertiary care service hospital were treated and evaluated for potential risk factors including prothrombotic factors and analysed using SPSS 15.0. Results: Mean age of patients of cerebral venous thrombosis (CVT), ischemic and hemorrhagic strokes in high altitude area (HAA) was 31.40, 38.68 and age of 38.60 years respectively. Mean Hemoglobin (Hb), homocysteine, serum protein C and S, and antithrombin III levels of HAA ischemic strokes patient was significantly higher than non high altitude area (NHAA) Patients. In case of CVT the difference in mean Serum protein S level of HAA and NHAA patients was significant. There was no statistical difference observed in mean values of serum homocysteine, protein C, protein S and antithrombin III among ischemic stroke and CVT patients in HAA. Conclusions: Prothrombotic state in case of CVT and ischemic strokes is an important risk factor in case for strokes among young individuals in HAA.